Powstanie Zakładu Historii Administracji Uniwersytetu Wrocławskiego - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The author presents the origins and circumstances of the creation of the Department of History of Administration at the University of Wrocław, the first failed attempts of its establishment in 1970 and 1972 and a successful completion in 1984. The author discusses it against the background of the emergence and development of similar research units in Poland and the role and importance of history of administration as an academic discipline, its place among historical and legal subjects and as one of the subjects of teaching in the context of administrative studies. It is associated with organizational and didactic changes that took place during this period at the Faculty of Law and Administration at the University of Wrocław, which ultimately led to the establishment of the Department. The author also shows the role played in the creation of that Department by the leadership of the Institute of History of State and Law, and especially prof. Alfred Konieczny, the initiator of creation and the first head of this Department.
Keywords: historia administracji; Instytut Historii Państwa i Prawa; Katedra Historii Administracji; studia na kierunku administracja